PUSAT KEBUDAYAAN TIONGHOA DI KOTA SINGKAWANG - Marsella, Marsella; Purnomo, Yudi; Affrilyno, Affrilyno (JMARS: Jurnal Mosaik Arsitektur, 2025)
Singkawang City is a city located in West Kalimantan Province, known for its significant population of ethnic Chinese residents, making it one of the largest ethnic Chinese communities in Indonesia. Cultural heritage from the ethnic Chinese community is easily found in Singkawang City, ranging from traditions, cuisine, to buildings with a distinct Chinese flair. This has led to Singkawang City joining the Indonesian Heritage Cities Network (JKPI), prompting the Singkawang City Government to begin planning areas that can be used to preserve Chinese cultural heritage. The planning of Chinese cultural areas in Singkawang City is a solution to existing issues. The existence of this design is intended to develop and preserve the existing Chinese cultural heritage in the urban area. The design method used is J.C. Jones' (1989) design method, which consists of ideas, information, analysis, synthesis, evaluation, and optimization. The design of this cultural center area will utilize the concept of a living museum. The results of the design will be divided into three spatial hierarchies: main spaces (traditional Chinese houses, performance buildings, thematic pedestrian paths), supporting spaces (public and green open spaces, informal economic zones, temporary festival zones), and complementary spaces (art and cultural installations, cultural facades for buildings, city parking, river bridges, public toilets). This design is realized by integrating existing cultural heritage into the area in accordance with the current physical conditions of the site, thereby creating an area that can interpret Chinese cultural values within it.